International Trade and International Finance Explorations of Contemporary Issues - Roy, Malabika; Sinha Roy, Saikat; SpringerLink (Online service) (New Delhi : Springer India (Imprint), 2016)
This book brings together a collection of papers on international trade and international finance, instead of treating the two as disjoint fields of study. The volume, while focusing on the recent developments and frontiers of research in international trade and international finance, also emphasizes the inherent integrated nature of the two subjects; some of the papers are overlapping across the two areas. A unique feature of the proposed volume is that it unravels some new issues in addition to re-examining certain old issues in a new perspective and thus covers wide ranging issues with an emphasis on policy. The book covers issues mostly relating to emerging market economies, which has increasingly assumed importance in the context of globalization. The book contains some survey papers covering the frontiers of current knowledge on important themes like recent developments in trade theory and empirics, foreign exchange market, institutions in trade and finance, interrelation and interaction between international trade and international finance. The papers, fruit of rigorous and original research, are written by internationally and nationally reputed authors along with promising young researchers on the subjects. The book substantially contributes to the growing literature on issues relating to trade and international finance in emerging market economies and extends the frontiers of knowledge. The book is expected to have the widest possible readership comprising of advanced undergraduate and graduate students as well as senior researchers working in international trade and international finance.
Part 1: Recent Developments in Trade Theory and Empirics -- Chapter 1. The "New-New" Trade Theory: A review of the literature -- Chapter 2. Time Zones and FDI with Heterogeneous Firms -- Chapter 3. Firm Heterogeneity and Decision to Export: An exploration with India's Capital Goods Sector -- Chapter 4. IPR Regulatory Policy, Commercial Piracy and Entry modes of MNC: A Theoretical Analysis -- Part 2: International trade and institutions -- Chapter 5. International Trade and Size of the Government -- Chapter 6. Heterogenous Effect of Corruption on Bilateral Trade: Sectoral Gravity Analysis with Panel Data -- Chapter 7. Enlargement Decisions of Regional Trading Blocs -- Chapter 8. The Deal Breaker or the Protector of Interests of Developing Countries: India's Changing Negotiating Stance in WTO -- Part 3: Issues in Trade, Trade Policy and Development -- Chapter 9. Export Performance in Textile and Garments with China as a Competitor: An analysis of India's situation from the perspective of Structure-Conduct-Performance paradigm -- Chapter 10. Impact of Trade Liberalization on Indian Textile Firms: A Panel Analysis -- Chapter 11. Trade, Infrastructure and Income Inequality in Selected Asian Countries: An empirical analysis -- Chapter 12. A Theoretical Model of Trade, Quality of Health Services and Signalling -- Chapter 13. Smuggling and Trafficking of Workers: A brief review and analysis of the Economics of Illegal Migration -- Chapter 14. Impact of Trade vs Non-Trade Policies on the Incidence of Child Labour: A Two Sector General Equilibrium Framework -- Chapter 15. FDI and Child Labour in a Developing Economy: A General Equilibrium Analysis -- Part 4: Issues related to foreign investment flows -- Chapter 16. The Role of Institutions in Attracting US FDI -- Chapter 17. Does foreign direct investment promote capital accumulation? -- Chapter 18. Do macroeconomic indicators influence foreign direct investment in India? A Causality Analysis -- Chapter 19. The Nature of trading by Domestic and Foreign Institutional Investors: A Cross Country Analysis -- Part 5: Issues relating to Globalization, financial markets and financial instruments -- Chapter 20. Exploratory study of select commodity and equity index around 2008 -- Chapter 21. An empirical estimation of volatility clustering, volatility spillover and persistence in terms of half-life from a developed country USA to two emerging economy India and China -- Chapter 22. Post Crisis Global Financial Architecture and India -- Part 6: Issues related to foreign exchange market -- Chapter 23. Survey and benchmarking of Indian FX markets and types of intervention -- Chapter 24. The global foreign exchange market: crisis and beyond -- Chapter 25. 'The Impossible Trinity': Where does India stand? -- Part 7: Issues related to financial institutions -- Chapter 26. Insuring the Insurer: a game theoretic approach to regulatory design -- Chapter 27. Does skill matter in Mutual funds? How emerging markets differ from more developed markets/Mutual fund performance: An International Perspective -- Chapter 28. Determinants of foreign bank entry into emerging market economies -- Chapter 29. Banks, financial derivatives, and crises: a fourth generation model.
Keywords: International Economics; Macroeconomics; Trade; Finance